Education for sustainable use of cement based materials. (December 2018) - Schmidt, Wolfram; Alexander, Mark; John, Vanderley
Abstract: Structural design and application have always been linked to the compressive strength of concrete as the main relevant criterion. This was justifiable in the past, where concrete consisted of water, ordinary Portland cement and aggregates, but this concept is no longer relevant for modern and more sustainable cement and concrete. Despite these new developments, existing standards, guidelines and academic curricula have not been much updated and are still used worldwide. There is a need to change this situation by proper education of the users. This overview describes the challenges that arise at a user level from the higher complexity of modern concrete, and defines needs and requirements for enhanced applicability of sustainable concrete concepts. Furthermore, recommendations are given on how better concrete practice can be communicated to all the involved parties, from civil and design engineers to constructors and site-appliers on the construction site.